Implementation of Geographic Information System Based on Google Maps API to Map Waste Collection Point Using the Haversine Formula Method - Ni Made Ary Esta Dewi Wirastuti; Lino Verlin; Is-Haka Mkwawa; Khalid G. Samarah (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
Human life with all its activities cannot be separated from the existence of waste but the quality of post-consumption waste is generally still low. To convert waste into a more stable form and does not pollute the environment, it is required a precise waste collection system. Waste collection system is an important part of waste management. This study is proposed a geographic information system (GIS) application based on google maps Application Programming Interface (API) to map waste collection point using Haversine formula method. The application is designed to develop a waste collection system from households to Temporary Disposal Sites (TDS), quickly and accurately. The application can be used by households and waste taxi bike drivers to communicate when the households need the taxi bike drivers to pick the waste up to the temporary collection points. A geographic information system application based on google maps API used to display the location of the taxi bike driver, TDS and the location of the waste collection (household). Haversine formula is used to get the nearest waste taxi bike driver to the location of the request for waste transportation. The result of this research is an application that can monitor and track waste collection. Using black box testing, the system has run according to the functions and scenarios designed. Based on the testing the system usability scale results, the application obtains a score of 70.125 which indicates that the application is classified as good and acceptable to users.